A cloud-based systematic cyber security teaching and learning framework for high school students - Contreras Vargas Berioska; Virtanen Seppo (Inderscience Publishers, 2025)
We present a systematic framework to construct cybersecurity knowledge for high school students on cloud computing. The learning outcomes were analysed based on time and completion rates to evaluate a ranking, learning curves, and clusters. The presented cyber security education module consists of a series of adaptive assignments anchored on constructivist and scaffolding learning theories. The probability of success for active guided tasks was 0.80. In the case of constructive adaptive assignments it was 0.75, and for interactive adaptive assignments it was 0.25. The completion rate dropped in the last adaptive assignment, implying the need to reinforce interactions earlier. Students demonstrated that motivation is as much determinant as the background experience, showing noticeable variations in the time needed to complete our adaptive assignments.